When I Am Old: The Self-Face Recognition Advantage Disappears for Old Self-Faces - Zhang, Ronghua; Zhou, Aibao (Frontiers in Psychology, 2019)
The self-face is the unique representation of oneself, and it has a processing advantage over familiar faces and the faces of strangers. Generally, recognition of the self-face is significantly faster or more accurate in a variety of tasks compared with recognizing others’ faces. While previous studies that used the present self-face as stimuli have found a processing advantage, what happens when the self-face turns old? To investigate whether an old self-face can still produce the processing advantage, we conducted two experiments. Experiment 1 used a standard visual search paradigm and Experiment 2 used the implicit association test. In both experiments, the old self-face was compared with the present self-face or an old friend-face. We found that when the self-face turns old, the processing advantage disappears. This research demonstrates a new way to investigate the future self.